Strategic entrepreneurship and dynamic flexibility: towards an integrative framework - Pereira, R. (2019)
Strategic entrepreneurship is a growing field within both Entrepreneurship and Management Science. Dynamic flexibility is a concept originally developed to resolve general business issues (Apter, 1985) and later enhanced to address specific strategic management challenges. Strategic Entrepreneurship deals with a singular strategic management response which is to achieve superior performance via simultaneous opportunity-seeking and advantage-seeking activities (Ireland, Hitt, & Simon, 2003). The process of maintaining superior performance is certainly a longitudinal one and requires capabilities on both those dimensions (Ireland & Webb, 2007). In this paper, we propose the use of dynamic flexibility as a useful capability to address strategic entrepreneurship longitudinal issue. By exploring the modulation time response model and different other references from both strategic management and strategic entrepreneurship literature, we aim to establish an integrative framework for dynamic strategic entrepreneurship.